TPU (thermoplastic polyurethane) material and preparation process thereof
Through the use of multi -efficiency auxiliary agents such as modified uneven rod soil, carbon nanotubes, and silicon dioxide, combined with the modification of dopamine and boric acid, the problem of insufficient anti -static and flame retardability of TPU materials, realizing the TPU material Comprehensive performance improvement.
Patent Information
- Application Number
- CN202411684369.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing TPU materials have shortcomings in their antistatic and flame retardant properties, and it is difficult to meet the high requirements of these performances in the electronics industry.
By using multi -efficiency auxiliary agents, including modified bump soil, carbon nanotubes, and silicon dioxide, combined with dopamine and boric acid modification treatment to improve the anti -static and flame retardant performance of TPU materials.
The good anti -static and flame retardant effects of TPU materials have been realized, and their mechanical properties are improved, which is suitable for preparation of related materials in the electronics industry.
Smart Images

Figure BDA0005149076680000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new material preparation, and specifically relates to a TPU material and a preparation process. Background Art
[0002] TPU is a thermoplastic polyurethane material composed of two groups, soft and hard. This unique two-phase structure gives TPU good mechanical properties and chemical resistance. Due to its excellent elasticity, tensile strength, wear resistance, tear resistance and chemical resistance, TPU is widely used in the fields of automobiles, machinery, medical treatment, footwear, electronic appliances, etc., and is used to manufacture various wear-resistant and impact-resistant parts and products. For example, in the production process of lithium batteries, in order to avoid friction and collision between materials when the robot arm grabs the lithium battery materials, TPU materials are often required for isolation. Therefore, TPU materials are required to have certain antistatic and wear-resistant properties. In fact, in the use of other fields such as automobiles and footwear, flame retardancy is a performance indicator that cannot be ignored. Therefore, it is very necessary to obtain TPU materials with antistatic and flame retardancy.
[0003] In the prior art, patent document CN106751716A provides a transparent antistatic TPU film and its preparation method and application, which is composed of TPU particles, epoxy resin, polycarbonate particles, K glue, carbon nanotubes, glass fiber, and antioxidant. By using the above substances, the raw material components of the TPU film cooperate with each other and work synergistically, so that the transparency of the TPU film is 6-8mm, the tensile strength is 72-77MPa, and the elongation at break is 365-390%, and higher transparency, better antistatic performance and good mechanical properties are obtained. However, the above patents do not pay attention to the flame retardancy of the material. Similarly, CN106003948A and CN103834051A only pay attention to the antistatic performance.
[0004] For example, patent document CN104861637A provides a mixing method for flame-retardant TPU cable materials, which consists of 100 parts of TPU raw material A, 6-12 parts of TCEP flame retardant B, 8-12 parts of DMMP flame retardant C, 5-10 parts of APP flame retardant D, and 5-10 parts of zinc borate flame retardant E. The cable material prepared based on the above raw materials has good flame retardant properties, but no attention is paid to antistatic properties.
[0005] For example, patent document CN114836023A provides a flame retardant and antistatic TPU composite material, the raw materials used are calculated by weight: 1-3 parts of expandable graphene oxide, 3-6 parts of ammonium polyphosphate, 5-8 parts of triphenyl boroxine, 85-90 parts of TPU particles, and 90 parts of DMF; boron flame retardants, carbon materials, etc. are used as flame retardants, and the flame retardant performance is good. The triphenyl boroxine used has good dispersibility in the TPU material, and can play a synergistic role with expandable graphene oxide, and has good antistatic performance. However, it can be seen that a large amount of DMF solvent is used, and the antistatic and flame retardant properties need to be further improved.
[0006] Therefore, the present invention has conducted relevant research around the improvement of the antistatic property and flame retardancy of TPU materials. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a TPU material and a preparation process, wherein the prepared TPU material has good flame retardancy, good antistatic property, good mechanical property and excellent comprehensive performance.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] In a first aspect, the present invention provides a TPU material, which is prepared from the following raw materials in parts by weight: 80 to 120 parts of TPU, 20 to 35 parts of multi-effect additives, 0.2 to 2.5 parts of antioxidants, and 0.2 to 2 parts of heat stabilizers;
[0010] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0011] S11, pre-modification of attapulgite: the attapulgite and sodium hydroxide are mixed evenly and then subjected to high temperature treatment. After the treatment is completed, the attapulgite is crushed to obtain pre-modified attapulgite;
[0012] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid, heating and stirring, centrifugation and washing to neutrality, and drying to obtain secondary modified attapulgite for later use;
[0013] S13, adding the carbon nanotubes to concentrated nitric acid for acidification treatment, washing after the treatment, then adding to water, then adding KH550, treating under heating conditions, filtering, washing, and drying after the treatment, to obtain modified carbon nanotubes;
[0014] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 into a buffer solution containing dopamine, soaking them, and then centrifuging and filtering them to obtain a composite material;
[0015] S15, placing silicon dioxide in a mixed solution for treatment, and washing it after the treatment is completed to obtain modified silicon dioxide for standby use;
[0016] S16, adding the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, treating them under heating conditions, and washing, drying and crushing them after the treatment to obtain a multi-effect additive.
[0017] Preferably, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168;
[0018] The heat stabilizer is selected from one or both of calcium stearate and zinc stearate.
[0019] Preferably, in step S11, the mass ratio of attapulgite to sodium hydroxide is 1:0.35-0.65; the high temperature treatment temperature is 780-805°C, and the treatment time is 0.5-4h.
[0020] Preferably, in step S12, the concentration of boric acid in the ethanol solution is 0.04-0.08 g / mL; the mass ratio of boric acid to pre-modified attapulgite is 1:1.5-2.8; the heating and stirring treatment temperature is 60-75°C, and the treatment time is 5-10 min;
[0021] Preferably, in step S13, the usage ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g: 4-8 g: 0.5-0.8 mL: 12-20 mL; the concentration of concentrated nitric acid is 4-6.5 mol / L;
[0022] The acidification treatment temperature is 55-75°C and the treatment time is 0.5-4h;
[0023] The heating temperature is 65 to 85°C, and the treatment time under the heating condition is 1 to 4 hours.
[0024] Preferably, in step S14, the dopamine-containing buffer is obtained by mixing Tris-HCl buffer and dopamine hydrochloride in a mass ratio of 1:1; the pH value of the dopamine-containing buffer is 7.8 to 8.5;
[0025] The dosage ratio of the secondary modified attapulgite, the buffer solution containing dopamine, and the modified carbon nanotubes is 1 g: 5-10 mL: 0.25-0.5;
[0026] The soaking treatment temperature is room temperature and the treatment time is 8 to 16 hours.
[0027] Preferably, in step S15, the mixed solution is obtained by mixing concentrated sulfuric acid and hydrogen peroxide solution in a volume ratio of 7:3; the amount ratio of silicon dioxide to the mixed solution is 1 g: 4-12 mL; the treatment temperature is room temperature, and the treatment time is 0.5-4 h.
[0028] Preferably, in step S16, the mass ratio of the composite material, modified silicon dioxide and water is 1:0.25-0.45:8-15; the heating temperature is 30-40°C, and the processing time is 2-6h.
[0029] In a second aspect, the present invention provides a process for preparing the above-mentioned TPU material, comprising the following steps:
[0030] Weigh each raw material component in proportion and mix them evenly, then send them into a twin-screw granulator for granulation.
[0031] Preferably, the processing temperature of the twin-screw granulator is 160-175°C, and the screw speed is 120-200rpm. It can be understood that the above processing temperature meets the actual requirements of TPU processing, and the temperature of each zone of the twin-screw granulator is not strictly limited in the present invention, and it is subject to adjustment by those skilled in the art.
[0032] It should be particularly noted that after extrusion, the obtained masterbatch can be processed accordingly according to the needs of the application scenario to obtain the desired TPU product, and the application form and scenario are not limited in the present invention.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The TPU material provided by the present invention has good antistatic and flame retardant effects and has good application value in the preparation of relevant materials in the electronics industry.
[0035] The TPU material provided by the present invention has antistatic and flame retardant properties by using a multi-effect auxiliary agent. Specifically, the multi-effect flame retardant uses carbon nanotubes, which have a low surface charge density and excellent antistatic properties; attapulgite and silicon dioxide have good high-heat resistance, and can form a dense film structure when filled between TPU particles, effectively preventing the circulation of oxygen and achieving a flame retardant effect; however, the above particles still have some shortcomings when used, such as carbon nanotubes, although having very good performance, are very easy to agglomerate, thereby reducing the performance in use. Similarly, attapulgite and silicon dioxide have poor compatibility with TPU particles. Therefore, the present invention has some disadvantages when used. During the process, the above raw materials were modified to a certain extent. For example, the attapulgite was first treated with high-temperature alkali melting to improve its activity on the one hand and enrich its pores on the other hand, which was beneficial to the subsequent modification of boric acid and the deposition of dopamine; then the attapulgite was modified with boric acid, one purpose of which was to introduce boron elements to improve the flame retardant properties, and the other purpose was to improve the effect of subsequent dopamine deposition based on some hydroxyl groups introduced by the boric acid modification; finally, the attapulgite was treated with dopamine, which has very rich hydroxyl and amino groups and good compatibility with TPU particles. Its introduction on the surface of attapulgite can greatly improve the dispersibility and compatibility of attapulgite;
[0036] In the present application, attapulgite and modified carbon nanotubes are treated together by optimizing the treatment conditions, thereby shortening the treatment process. The carbon nanotubes are firstly subjected to an acid treatment, which is beneficial for introducing functional groups such as carboxyl and hydroxyl groups to improve their activity. Then, KH550 is introduced for treatment. The hydrolysis of KH550 forms hydroxyl groups which, on the one hand, will form hydrogen bonds with the acidified carbon nanotubes. On the other hand, the hydroxyl groups and amino groups contained in KH550 will also combine with the subsequent dopamine, which is beneficial for improving the deposition modification of dopamine.
[0037] In order to improve the dispersibility of silica in the present application, a simple mixed acid treatment is performed on it to introduce hydroxyl groups, so as to form a large filling system based on hydrogen bonds and other forms of effects with attapulgite and carbon nanotubes modified with dopamine, thereby densely filling, improving the film-forming effect, and maximizing the flame retardant and antistatic effects.
[0038] In summary, the present invention gives the TPU material excellent comprehensive properties (good mechanical properties) through modification by preferably using silicon dioxide, attapulgite and carbon nanotubes. DETAILED DESCRIPTION
[0039] Embodiments of the present invention are described in detail below. All embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0040] Unless otherwise specified, the chemical reagents and production equipment involved in the present invention are purchased from the market.
[0041] Among them, attapulgite was purchased from Changzhou Naou New Material Technology Co., Ltd.
[0042] Silicon dioxide was nano-silicon dioxide purchased from Shanghai Huijing Nano New Materials Co., Ltd.;
[0043] Carbon nanotubes were purchased from Jiaxing Naco New Materials Co., Ltd., with a length of 10 μm and a tube diameter of about 50 nm;
[0044] TPU was purchased from Yantai Wanhua with the brand name WHT-1565IC.
[0045] The concentration of concentrated sulfuric acid is 98 wt % and the concentration of hydrogen peroxide is 30 wt %.
[0046] Example 1
[0047] A TPU material is prepared from the following raw materials by weight: 100g TPU, 30g multi-effect additive, 1.5g antioxidant 1010, and 2g zinc stearate.
[0048] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0049] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.45 and then subjected to high temperature treatment (790°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0050] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid (0.05 g / mL) at a mass ratio of 2.5:1, heating and stirring (65°C, 8 min), centrifugally filtering, washing to neutrality and drying to obtain secondary modified attapulgite for later use;
[0051] S13, adding carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (60°C, 0.5 h), washing after the treatment, then adding to water, then adding KH550, and treating under heating conditions (75°C, 1 h), after the treatment, filtering, washing, and drying to obtain modified carbon nanotubes; wherein the amount ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g: 5 g: 0.55 mL: 15 mL;
[0052] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 to a dopamine-containing buffer solution (Tris-HCl buffer solution and dopamine hydrochloride are mixed in a mass ratio of 1:1, and the pH value is 8), soaking them (room temperature, 12 hours), and centrifuging and filtering them to obtain a composite material; wherein the amount ratio of the secondary modified attapulgite, the dopamine-containing buffer solution, and the modified carbon nanotubes is 1g:8mL:0.35;
[0053] S15, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) according to a dosage ratio of 1:6 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0054] S16. Add the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, and treat them under heating conditions (35°C, 4h). After the treatment, wash, dry and crush them to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.3:10.
[0055] In this embodiment, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing each raw material component in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0056] Example 2
[0057] A TPU material is prepared from the following raw materials by weight: 100g TPU, 28g multi-effect additive, 1.8g antioxidant 1010, and 1.8g zinc stearate.
[0058] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0059] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0060] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid (0.04 g / mL) at a mass ratio of 2.5:1, heating and stirring (60°C, 10 min), centrifugally filtering, washing to neutrality and drying to obtain secondary modified attapulgite for later use;
[0061] S13, adding carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (65°C, 0.5 h), washing after the treatment, then adding to water, then adding KH550, and treating under heating conditions (75°C, 1 h), after the treatment, filtering, washing, and drying to obtain modified carbon nanotubes; wherein the amount ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g:4.5 g:0.58 mL:12 mL;
[0062] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 to a dopamine-containing buffer solution (Tris-HCl buffer solution and dopamine hydrochloride are mixed in a mass ratio of 1:1, and the pH value is 8), soaking them (room temperature, 12 hours), and centrifuging and filtering them to obtain a composite material; wherein the amount ratio of the secondary modified attapulgite, the dopamine-containing buffer solution, and the modified carbon nanotubes is 1g:8mL:0.38;
[0063] S15, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) according to a dosage ratio of 1:7 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0064] S16. Add the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, and treat them under heating conditions (35°C, 3.5h). After the treatment, wash, dry and crush to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.28:10.
[0065] In this embodiment, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing each raw material component in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0066] Example 3
[0067] A TPU material is prepared from the following raw materials by weight: 100g TPU, 28g multi-effect additive, 2.2g antioxidant 1010, and 1.9g zinc stearate.
[0068] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0069] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.5 and then subjected to high temperature treatment (795°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0070] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid (0.06 g / mL) at a mass ratio of 2.3:1, heating and stirring (60°C, 10 min), centrifugally filtering, washing to neutrality and drying to obtain secondary modified attapulgite for later use;
[0071] S13, adding carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (65°C, 0.5 h), washing after the treatment, then adding to water, then adding KH550, and treating under heating conditions (75°C, 1 h), after the treatment, filtering, washing, and drying to obtain modified carbon nanotubes; wherein the amount ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g:4.6 g:0.62 mL:12 mL;
[0072] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 to a dopamine-containing buffer solution (Tris-HCl buffer solution and dopamine hydrochloride are mixed in a mass ratio of 1:1, and the pH value is 8), soaking them (room temperature, 12 hours), and centrifuging and filtering them to obtain a composite material; wherein the amount ratio of the secondary modified attapulgite, the dopamine-containing buffer solution, and the modified carbon nanotubes is 1g:8mL:0.42;
[0073] S15, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) according to a dosage ratio of 1:7 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0074] S16. Add the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, and treat them under heating conditions (35°C, 4.5h). After the treatment, wash, dry and crush them to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.32:10.
[0075] In this embodiment, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing each raw material component in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0076] Comparative Example 1
[0077] Compared with Example 1, the boric acid modification of attapulgite is not performed in Comparative Example 1, that is, step S12 is omitted. Specifically, in Comparative Example 1, a TPU material is provided, which is prepared from the following raw materials by weight: 100g TPU, 30g multi-effect additive, 1.5g antioxidant 1010, and 2g zinc stearate.
[0078] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0079] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.45 and then subjected to high temperature treatment (790°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0080] S12, adding carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (60°C, 0.5 h), washing after the treatment, then adding to water, then adding KH550, and treating under heating conditions (75°C, 1 h), after the treatment, filtering, washing, and drying to obtain modified carbon nanotubes; wherein the amount ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g: 5 g: 0.55 mL: 15 mL;
[0081] S13, adding the pre-modified attapulgite obtained in step S11 and the modified carbon nanotubes obtained in step S12 to a dopamine-containing buffer solution (Tris-HCl buffer solution and dopamine hydrochloride are mixed in a mass ratio of 1:1, and the pH value is 8), soaking them (room temperature, 12 hours), and centrifuging and filtering them to obtain a composite material; wherein the amount ratio of the pre-modified attapulgite, the dopamine-containing buffer solution, and the modified carbon nanotubes is 1g:8mL:0.35;
[0082] S14, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) at a dosage ratio of 1:6 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0083] S15. Add the composite material obtained in step S13 and the modified silicon dioxide obtained in step S14 into water, and treat them under heating conditions (35°C, 4h). After the treatment, wash, dry and crush them to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.3:10.
[0084] In this comparative example, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing the raw material components in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0085] Comparative Example 2
[0086] Compared with Example 1, KH550 is not used in the treatment process of step S13 in Comparative Example 2. Specifically, in Comparative Example 2, a TPU material is provided, which is prepared from the following raw materials by weight: 100g TPU, 30g multi-effect additive, 1.5g antioxidant 1010, and 2g zinc stearate.
[0087] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0088] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.45 and then subjected to high temperature treatment (790°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0089] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid (0.05 g / mL) at a mass ratio of 2.5:1, heating and stirring (65°C, 8 min), centrifugally filtering, washing to neutrality and drying to obtain secondary modified attapulgite for later use;
[0090] S13, adding the carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (60°C, 0.5 h), washing and drying after the treatment, to obtain modified carbon nanotubes; wherein the amount ratio of the carbon nanotubes, concentrated nitric acid, and water is 1 g: 5 g: 15 mL;
[0091] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 to a dopamine-containing buffer solution (Tris-HCl buffer solution and dopamine hydrochloride are mixed in a mass ratio of 1:1, and the pH value is 8), soaking them (room temperature, 12 hours), and centrifuging and filtering them to obtain a composite material; wherein the amount ratio of the secondary modified attapulgite, the dopamine-containing buffer solution, and the modified carbon nanotubes is 1g:8mL:0.35;
[0092] S15, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) according to a dosage ratio of 1:6 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0093] S16. Add the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, and treat them under heating conditions (35°C, 4h). After the treatment, wash, dry and crush them to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.3:10.
[0094] In this comparative example, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing the raw material components in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0095] Comparative Example 3
[0096] Compared with Example 1, dopamine is not used in the treatment process of step S14 in Comparative Example 3, but water is used instead. Specifically, in Comparative Example 3, a TPU material is provided, which is prepared from the following raw materials by weight: 100g TPU, 30g multi-effect additive, 1.5g antioxidant 1010, and 2g zinc stearate.
[0097] Wherein, the preparation of the multi-effect additive comprises the following steps:
[0098] S11. Pre-modification of attapulgite: attapulgite and sodium hydroxide are mixed evenly in a mass ratio of 1:0.45 and then subjected to high temperature treatment (790°C, 0.5h). After the treatment is completed, the pre-modified attapulgite is obtained by pulverizing.
[0099] S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid (0.05 g / mL) at a mass ratio of 2.5:1, heating and stirring (65°C, 8 min), centrifugally filtering, washing to neutrality and drying to obtain secondary modified attapulgite for later use;
[0100] S13, adding carbon nanotubes to concentrated nitric acid (6 mol / L) for acidification treatment (60°C, 0.5 h), washing after the treatment, then adding to water, then adding KH550, and treating under heating conditions (75°C, 1 h), after the treatment, filtering, washing, and drying to obtain modified carbon nanotubes; wherein the amount ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g: 5 g: 0.55 mL: 15 mL;
[0101] S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 into water, soaking them (room temperature, 12 hours), and centrifugation filtering them to obtain a composite material; wherein the amount ratio of the secondary modified attapulgite, water, and modified carbon nanotubes is 1g:8mL:0.35;
[0102] S15, placing silicon dioxide in a mixed solution (concentrated sulfuric acid and hydrogen peroxide solution mixed in a volume ratio of 7:3) according to a dosage ratio of 1:6 mL for treatment (room temperature, 0.5 h), and washing after the treatment to obtain modified silicon dioxide for standby use;
[0103] S16. Add the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, and treat them under heating conditions (35°C, 4h). After the treatment, wash, dry and crush them to obtain a multi-effect additive; wherein the mass ratio of the composite material, the modified silicon dioxide and water is 1:0.3:10.
[0104] In this embodiment, a preparation process of the above-mentioned TPU material is also provided, comprising the following steps: weighing each raw material component in proportion and mixing them evenly, and then sending them into a twin-screw granulator for granulation (processing temperature is 170°C, rotation speed is 120rpm).
[0105] The performance test of the TPU materials obtained in Example 1 and Comparative Examples 1 to 3 was carried out as follows:
[0106] The antistatic performance is carried out in accordance with GBT 1410-2006; the flame retardant performance is carried out in accordance with UL-94 standard; the elongation at break is carried out in accordance with GB / T1040.1-2018; and the tensile performance is carried out in accordance with GB / T1040.1-2018.
[0107] The test results are shown in Table 1.
[0108] Table 1 Test results
[0109]
[0110] It can be seen from Table 1 that the TPU material prepared by the present invention has good flame retardancy, good antistatic performance, and excellent mechanical properties.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A TPU material, characterized in that: The method is prepared from the following raw materials in parts by weight: 80 to 120 parts of TPU, 20 to 35 parts of multi-effect additives, 0.2 to 2.5 parts of antioxidants, and 0.2 to 2 parts of heat stabilizers; Wherein, the preparation of the multi-effect additive comprises the following steps: S11, pre-modification of attapulgite: the attapulgite and sodium hydroxide are mixed evenly and then subjected to high temperature treatment. After the treatment is completed, the attapulgite is crushed to obtain pre-modified attapulgite; S12, adding the pre-modified attapulgite obtained in step S11 to an ethanol solution containing boric acid, heating and stirring, centrifugation and then washing to neutrality and drying to obtain secondary modified attapulgite for later use; S13, adding the carbon nanotubes to concentrated nitric acid for acidification treatment, washing after the treatment, then adding to water, then adding KH550, treating under heating conditions, filtering, washing, and drying after the treatment, to obtain modified carbon nanotubes; S14, adding the secondary modified attapulgite obtained in step S12 and the modified carbon nanotubes obtained in step S13 into a buffer solution containing dopamine, soaking them, and then centrifuging and filtering them to obtain a composite material; S15, placing silicon dioxide in a mixed solution for treatment, and washing it after the treatment is completed to obtain modified silicon dioxide for standby use; S16, adding the composite material obtained in step S14 and the modified silicon dioxide obtained in step S15 into water, treating them under heating conditions, and washing, drying and crushing them after the treatment to obtain a multi-effect additive.
2. A TPU material according to claim 1, characterized in that: The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168; The heat stabilizer is selected from one or both of calcium stearate and zinc stearate.
3. A TPU material according to claim 1, characterized in that: In step S11, the mass ratio of attapulgite to sodium hydroxide is 1:0.35-0.65; the high temperature treatment temperature is 780-805°C, and the treatment time is 0.5-4h.
4. A TPU material according to claim 2, characterized in that: In step S12, the concentration of boric acid in the ethanol solution is 0.04-0.08 g / mL; the mass ratio of boric acid to pre-modified attapulgite is 1:1.5-2.8; the heating and stirring treatment temperature is 60-75°C, and the treatment time is 5-10 min.
5. A TPU material according to claim 1, characterized in that: In step S13, the usage ratio of carbon nanotubes, concentrated nitric acid, KH550, and water is 1 g: 4-8 g: 0.5-0.8 mL: 12-20 mL; the concentration of concentrated nitric acid is 4-6.5 mol / L; The acidification treatment temperature is 55-75°C and the treatment time is 0.5-4h; The heating temperature is 65 to 85°C, and the treatment time under the heating condition is 1 to 4 hours.
6. A TPU material according to claim 1, characterized in that: In step S14, the dopamine-containing buffer solution is obtained by mixing Tris-HCl buffer solution and dopamine hydrochloride in a mass ratio of 1:1; the pH value of the dopamine-containing buffer solution is 7.8-8.5; The dosage ratio of the secondary modified attapulgite, the buffer solution containing dopamine, and the modified carbon nanotubes is 1 g: 5-10 mL: 0.25-0.5; The soaking treatment temperature is room temperature and the treatment time is 8 to 16 hours.
7. A TPU material according to claim 2, characterized in that: In step S15, the mixed solution is obtained by mixing concentrated sulfuric acid and hydrogen peroxide solution in a volume ratio of 7:3; the amount ratio of silicon dioxide to the mixed solution is 1g:4-12mL; the treatment temperature is room temperature, and the treatment time is 0.5-4h.
8. A TPU material according to claim 2, characterized in that: In step S16, the mass ratio of the composite material, modified silicon dioxide and water is 1:0.25-0.45:8-15; the heating temperature is 30-40°C, and the processing time is 2-6 hours.
9. A process for preparing the TPU material according to any one of claims 1 to 8, characterized in that: The steps include: Weigh each raw material component in proportion and mix them evenly, then send them into a twin-screw granulator for granulation.
10. The preparation process according to claim 9, characterized in that: The processing temperature of the twin-screw granulator is 160-175°C, and the screw speed is 120-200rpm.
Citation Information
Patent Citations
Barrier anti-static TPU (Thermoplastic Polyurethane) composite material film and preparation method thereof
CN103834051A
Flame-retard TPU cable material mixing method
CN104861637A
Antistatic TPU (Thermoplastic Polyurethane) film
CN106003948A
Transparent antistatic TPU thin film, and preparation method and application thereof
CN106751716A
Flame-retardant antistatic TPU composite material
CN114836023A